Students' Voices on the Involvement of Social Workers in Services Related to Problematic Internet Use. Issue 3 (27th May 2018) - Geyer, Stephan; Le Roux, Liana; Hall, Herna
Abstract : Worldwide the internet is increasingly used for personal, academic and work-related purposes. Extensive internet use could result in Problematic Internet Use (PIU). Students, often young adults, are identified as a potential risk group for PIU. Social work has a long history of involvement with services related to addiction and PIU falls within this domain. A hiatus was identified in terms of the voice of students, as service users, on the involvement of social workers in services related to PIU within the university environment. Based on convenience sampling, a survey was undertaken with 498 second-year students enrolled for a basic social science course at a South African university. Data were collected by means of a survey, including an open-ended question, with the aim to explore students' perceptions of and suggestions for the involvement of social workers in services related to PIU. Based on the findings, integrated primary and secondary social work methods on the levels of prevention, early intervention, treatment and aftercare are recommended. Recommendations include awareness campaigns, community education, policy development, skills training, individual counselling, therapy groups and aftercare services to ensure the sustainability of the gains from previous interventions.